Organometallics and renewables - Weckhuysen, Bert M.; Bruijnincx, Pieter C. A.; Meier, Michael A.R (Topics in Organometallic Chemistry, 2012)
Lucas Montero de Espinosa and Michael A. R. Meier: Olefin Metathesis of Renewable Platform Chemicals.- Pieter C. A. Bruijnincx, Robin Jastrzebski, Peter J. C. Hausoul, Robertus J. M. Klein Gebbink, and Bert M. Weckhuysen: Pd-Catalysed Telomerisation of 1,3-Dienes with Multifunctional Renewable Substrates - Versatile Routes for the Valorisation of Biomass-Derived Platform Molecules.- A Behr, A. J. Vorholt: Hydroformylation and related reactions of renewable resources.- Ties J. Korstanje, Robertus J.M. Klein Gebbink: Catalytic oxidation and deoxygenation of renewables with rhenium complexes.- Antoine Buchard, Clare M. Bakewell, Jonathan Weiner and Charlotte K. Williams: Recent Developments In Catalytic Activation Of Renewable Resources For Polymer Synthesis.